AGROTOURISM BUSINESS STRATEGY WITH BUSINESS MODEL CANVAS APPROACH - Jessyka, Jessyka; Dolorosa, Eva; Suharyani, Anita (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
The rapid development in the world of tourism has become a special attraction for research, especially for agro-tourism businesses with a lot of potential. Therefore, a business model and strategy are needed that are appropriate and suitable for agro-tourism businesses by analyzing the strengths, weaknesses, opportunities, and threats currently being faced as well as developing a business model that will be implemented in the future based on the business model canvas. The research method uses a qualitative descriptive method with the research location at the Rekadena agrotourism business, which is located in Jeruju Besar Village, Kubu Raya Regency, West Kalimantan Province. The variable consist of customer segmnets, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. The result of the research are segmented consumer segmentation, channels run by agro-tourism in the form of communication, distribution, and direct selling, as well as providing personal assistance and relying on service quality. Rekadena's agro-tourism motivation in establishing partner relations is the acquisition of resources and activities. In addition, the cost structure of rekadena's agro-tourism shows that the biggest cost factor in the company is employee salaries.